Study on Dynamic Mechanical Behaviors and J–C Constitutive Model of a Fine-Grained D6A Steel - Zezhou Yang; Xiaowei Feng; Xiaoli Zhang; Yongfeng Shen; Xicheng Huang; Ruoze Xie (Crystals, 2022)
The uniaxial tensile loading tests of coarse-grained D6A steel (CG, d = 20 μm) and fine-grained D6A steel (FG, d = 1.5 μm) were performed using a material testing machine and rotating disk Hopkinson tension bar, respectively. The stress–strain curves of two steels at different strain rates (0.001~1500 s−1) were obtained. Results show that grain refinement effectively improves the strength of FG steel, which is achieved by high-density of grain boundaries and cementite particles hindering the movement of dislocations. In the strain rate range of the test, the strain rate sensitivity of FG D6A steel decreases, which is considered to be the result of the athermal stress that independent of the strain rate becomes the dominant part of the total stress. Combined with the experimental data, the parameters of the Johnson–Cook (J–C) constitutive model were calibrated. The stress–strain curves obtained by simulations are in good agreement with those from tests. These results may provide an important experimental reference and theoretical basis for the application of FG D6A steel in various fields.